2012
DOI: 10.1590/s0103-64402012000600009
|View full text |Cite
|
Sign up to set email alerts
|

Flexural properties, morphology and bond strength of fiber-reinforced posts: influence of post pretreatment

Abstract: The aim of this study was to assess the influence of surface pretreatments of fiber-reinforced posts on flexural strength (FS), modulus of elasticity (ME) and morphology of these posts, as well as the bond strength (BS) between posts and core material. Fifty-two fiber posts (smooth and serrated) were assigned to 4 groups (n=13): no treatment (control), 10% hydrogen peroxide (HP) for 10 min (HP-10), 24% HP for 1 min (HP-24) and airborne-particle abrasion (Al(2)O(3)). To evaluate FS and ME, a 3-point bending tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 21 publications
(47 reference statements)
1
23
0
5
Order By: Relevance
“…These results demonstrated that the relatively greater strength of the post-composite bond appeared to be stronger than the resin cement or GFP itself due to stress transfer. A study 33) shows that GFP treated with H2O2 might not impair the mechanical strength that need to be tested in future research.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that the relatively greater strength of the post-composite bond appeared to be stronger than the resin cement or GFP itself due to stress transfer. A study 33) shows that GFP treated with H2O2 might not impair the mechanical strength that need to be tested in future research.…”
Section: Discussionmentioning
confidence: 99%
“…[121427] Many studies have evaluated the effects of surface treatments on adhesion of fiber-reinforced posts to cores. [101112131415] Applying hydrogen peroxide on quartz fiber post is a conservative procedure for the enforcing of post-core interface. Previous studies have shown several advantages of this procedure for treatment of quartz fiber-post surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…This process enhances micromechanical retention on the surface of fiber post. [11] According to a study conducted by de Sousa Menezes et al ., application of hydrogen peroxide in different concentrations improves adhesion between fiber post and composite core. [12] Elseka,[13] Yenisey,[14] and Vano[15] reported that chemical surface treatment of post surface with hydrogen peroxide increases bond strength of quartz fiber post to composite resin core.…”
Section: Introductionmentioning
confidence: 99%
“…Silanes are coupling agents that can interact with both organic (resin) and inorganic (glass) phases; however, they have little ability to react with epoxy resin-based posts (4) and also great possibility to undergo hydrolysis, weakening their coupling stability (5). Consequently, studies diverge about the real benefit of silanization in improving post retention (6)(7)(8)(9)(10)(11); therefore, other substances have currently been investigated, such as resin adhesives (12), acid solutions (13)(14)(15), and hydrogen peroxide agents (16)(17)(18). Among these alternatives, the application of bleaching agents reached positive results (17,18), although there is a lack of information about the negative effects on the post structure that may occur.…”
mentioning
confidence: 99%